Grazing diverse combinations of tanniferous and nontanniferous legumes: implications for foraging behavior, performance, and hair cortisol in beef cattle. (17th October 2021) - Lagrange, Sebastian; MacAdam, Jennifer W; Stegelmeier, Bryan; Villalba, Juan J
Abstract: A diversity of forages with different types and concentrations of nutrients and plant secondary compounds may lead to complementary relationships that enhance cattle performance and welfare. We determined whether grazing combinations of tanniferous legumes ( Lotus corniculatus, birdsfoot trefoil [BFT], Onobrychis viciifolia, sainfoin [SF]), and alfalfa [ALF] ( Medicago sativa ) influence foraging behavior, performance, and hair cortisol concentration in beef cattle compared with grazing the same legumes as monocultures. Twenty-one pairs of heifers grazed three spatial replications of seven treatments: monocultures of BFT, SF, or ALF, and all possible two- and three-way choices among strips of these legumes: SF-BFT, ALF-BFT, ALF-SF, and ALF-SF-BFT in two periods of 25 d each (adaptation phase + experimental period) during two consecutive years. The lowest incidence of grazing events occurred in the BFT treatment (42.0% of the total scans recorded; P < 0.10), with the rest of the treatments ranging between 47.8% (SF-BFT) and 52.6% (ALF-SF) of the total scans recorded. Heifers selected a varied diet, preferring SF over BFT or ALF in a 46:27:27 ratio for the three-way choice, and in a 70:30 ratio for both two-way choices. Heifers preferred BFT over ALF (62:38 ratio) in a two-way choice. All treatments followed similar daily grazing patterns ( P > 0.10), with two major grazing events (1 h after sunrise and 3 h before dark). No differences among treatments were observed for the number of steps taken by heifers on a daily basis, motion index, or the percentage of time heifers spent standing (1, 599, 5, 356, and 45.3%, respectively; P > 0.10), suggesting that heifers on choice treatments did not invest extra time in walking, searching, or patch switching activities relative to heifers grazing monocultures. Heifers grazing the three-way choice gained more body weight (1.27 kg/d) than the average gains observed for animals grazing in all legume monocultures (1.00 kg/d; P = 0.014) or two-way choices (0.97 kg/d; P = 0.007), suggesting a synergism among pasture species for the treatment with the highest diversity. No differences in hair cortisol concentration were observed among treatments, with values ranging between 1.4 (BFT) and 2.12 ng/g (three-way choice; P > 0.10). Thus, forage diversity has the potential to enhance animal performance without affecting grazing efficiency, likely explained by the spatial arrangement of the forage species presented in the study.